Real-time determination of earthquake focal mechanism via deep learning - Wenhuan Kuang (Nature Portfolio, 2021)
The authors here present a deep learning method to determine the source focal mechanism of earthquakes in realtime. They trained their network with approximately 800k synthetic samples and managed to successfully estimate the focal mechanism of four 2019 Ridgecrest earthquakes with magnitudes larger than Mw 5.4.